Adapting and applying intervention mapping to integrate medical-legal partnership into organizations providing HIV care: an implementation methodology study - Muñoz-Laboy, Miguel; French, Ashley; Davison, Robin; Morton, Samantha J.; Arnold, Emily A.; Rudolph, Abby E.; Jones, Resa M.; Fernandez, M. Isabel; Martinez, Omar (Frontiers in Health Services, 2025)
BackgroundImplementation science in public health has facilitated the translation of research findings into effective public health programming and evidence-based policy decision-making. One of the most prominent implementation science methodologies is intervention mapping, briefly defined as a rigorous protocol that guides the design of multi-level health promotion interventions and implementation strategies. In this manuscript, we describe our use and adaption of intervention mapping in Medical-Legal Partnerships, which are an integration of comprehensive legal services within primary health care and social service spaces working to mitigate the effects of negative social determinants of health for persons with HIV (PWH).MethodsIntervention mapping in this study was modified from a six-step to a five-step approach by integrating Step 4 and Step 5 of the original version of intervention mapping. The rationale for combining Step 4 and 5 into one step was that coherent, independent intervention packages existed for the provision of legal and HIV services, and it was determined through Step 1 of intervention mapping that these two existing intervention approaches can be integrated at the organizational level but should remain collocated at the patient level. Thus, our modified intervention mapping steps consisted of: (1) conducted needs assessments among medical legal partnerships (MLP) programs (providers and patients) serving PWH in order to identify the current landscape of MLP adoption and implementation in HIV care contexts and common components of those programs; (2) generated organizational and practice-level implementation outcomes and objectives, determinants and change objectives matrices to guide each strategy; (3) chose methods and mechanisms of change of the overarching implementation strategy; (4) produced implementation protocols and materials; and (5) developed a plan to evaluate implementation outcomes.ResultsFollowing intervention mapping author recommendations that not every step is needed in intervention mapping, using our modified intervention mapping approach resulted in a comprehensive organizational level intervention. Applying our adapted intervention mapping process resulted in the intervention package, OPAHL (Organizational Partnerships for Healthy Living), which currently is being tested for feasibility and preliminary effectiveness in a hybrid, randomized cluster trial in Philadelphia, Pennsylvania.ConclusionsThe work presented here provides a practical framework that can be replicated by other researchers and practitioners working on the social epidemiology of chronic illness, communicable disease, and access to and engagement with care.